A potential of Jasminum sambac (L.) Aiton leaf nano-extract as spray treatment of gingivitis-induced Sprague Dawley rats - Nuryanti, Archadian; Larasati, Puspa Ayu Aprilia; Almeyda, Alda Risma; Marandof, Monica Agnesia; Irawan, Catherine Marcia (Faculty of Dentistry, Universitas Gadjah Mada, 2023)
Gingivitis is the second most common disease that occurs in the oral cavity. The use of chlorhexidine as a gingivitis therapy agent has some side effects such as allergic reactions and bacterial resistance. Jasminum Sambac (L.) Aiton leaf nano-extract contains flavonoids, saponins, and tannins compounds reported to have an influence on wound healing process. The aim of this research was to determine the effect of observation time and concentrations of Jasminum sambac (L.) Aiton leaf nano-extract on the number of neutrophils, macrophages, and angiogenesis in the treatment of gingivitis-induced Sprague Dawley rats. Sixty male Sprague Dawley rats aged 2.5-3 months with body weight of 200-250 g were anesthetized with ketamine HCl (10 mg/kg BW) and xylazine (2 mg/kg BW) then induced using silk ligature 3.0 on the interdental of the mandibular incisor. The rats were divided into five groups and got daily spray using distilled water (negative control), nano-extract at a concentration of 40%, 45%, 50%, and 0.12% chlorhexidine (positive control). The rats were euthanized on the 1st, 3rd, 5th, and 7th days post-treatment. The tissues were processed histologically with HE staining. The number of neutrophils, macrophages, and angiogenesis were counted using a microscope (400x) and OptiLab Viewer® (13x) at five fields of view. The result of the Two Way ANOVA test showed that there were significant effect of concentrations and observation time, and interaction of both observation time and concentrations on the number of neutrophils, macrophages, and angiogenesis (p < 0.05). It can be concluded that observation time and concentrations of Jasminum sambac (L.) Aiton leaf nano-extract affected the number of neutrophils, macrophage, and angiogenesis in the treatment of gingivitis-induced Sprague Dawley rat (p < 0.05).